Relationships between social support, dark triad and life satisfaction in honorary blood donors. The mediating role of emotional support - Kosowski, Paweł (Journal of Education, Health and Sport, 2023)
Background The psychological interest in the group of blood donors, in the perspective of worldwide research, is a valuable source of knowledge about variables that may help to attract new blood donors or to maintain the regularity of donations. So far, Polish research in this group has only investigated the state of knowledge about blood donation and has not studied specific psychological predispositions. The aim The aim of the presented study was to examine the relationship between the dark triad, social support and life satisfaction in a group of polish voluntary blood donors. Material and methods In order to measure variables of interest, the SD3 scale, the Social Support Scale, and the SWLS were used. The study included a group of 111 voluntary blood donors from different cities in Poland. Results The conducted analyses showed positive and significant relationships between social support (informational, material, emotional, and valuational), narcissism, and life satisfaction. Furthermore, linear regression analysis showed that social support and the dark triad explain life satisfaction in the study group by 30%. Mediation analysis showed that emotional support enhances the relationship of narcissism and life satisfaction. Conclusions The associations of narcissism, social support and life satisfaction can be explained through Caroll Ryff's theory of psychological well-being, according to which both subclinical narcissism and received social support can be components of a positive assessment of a person's quality of life. The study may provide a baseline for further research in a group of voluntary blood donors - e.g. with an extension of narcissism to include its communal dimension.